E-BANKING SYSTEM - Reshma K. Malgonde; Priya S. Ghadge, Renuka V. Pawar, Akanksha R. Mali (International Journal of Innovations in Engineering Research and Technology, 2022)
e-Banking System is mainly designed primarily function for use in the transfer online money. Electronic Banking is more commonly referred to as internet banking or simply net banking. This system will allow bank and organization to increase Customer such type of business. The customers can be transfer money just few minutes. In the e-Banking System allows to quickly and easily transfer money on any place. It is an electronic payment system supported by a website that offers an array of products and services of any bank that is possible to workelectronically, like payments, transfers, deposits and more.